ANALISIS SALURAN PEMASARAN IKAN MUJAIR DARI DESA TOMADO KECAMATAN LINDU KABUPATEN SIGI - Assagaf, Sarifah Humaira; M, Marhawati; Laapo, Alimudin (Fakultas Pertanian, Universitas Tadulako, 2023)
The marketing of Tilapia fish primarily takes place in Palu and its nearby areas. The selling price of tilapia at the producer or fisherman level in Tomado Village differs significantly from the price paid by the end consumer. This substantial price difference is attributed to the involvement of marketing agencies in the fish buying and distribution process. The objectives of the study: (i) to investigate the formation of marketing channels and marketing margins for tilapia fish, and (ii) to assess the level of efficiency and price received by fishermen in in Tomado village. The research was carried out in December 2019. The respondents were selected using a simple random sampling technique, resulting in 38 samples. The analysis involved three main approaches: Marketing Margin analysis, Marketing Efficiency analysis, and Farmers Share analysis. The study findings revealed the existence of two marketing channels for tilapia in Tomado Village. The marketing margin for the channel I was IDR 19,000, while for the channel II it was IDR 17,000. The marketing efficiency in channel I was 2.33%, whereas in channel II it was 3.60%. Furthermore, the share of the price received by fishermen, also known as Farmers Share, was 24% in the channel I and 32% in the channel II.